1987
DOI: 10.1038/bjc.1987.131
|View full text |Cite
|
Sign up to set email alerts
|

Selective necrosis of malignant gliomas in mice using photodynamic therapy

Abstract: Images Figure 2 Figure 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…An iron‐chelating agent can temporarily remove free Fe 2+ from the system, inhibiting its insertion into PpIX, thus preventing the formation of heme and as a result PpIX accumulates in the cell (19). Iron‐chelating agents which have been investigated in the past include ethylenediamine tetra acetic acid (EDTA) (20) and desferrioxamine (DFO) (21). Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…An iron‐chelating agent can temporarily remove free Fe 2+ from the system, inhibiting its insertion into PpIX, thus preventing the formation of heme and as a result PpIX accumulates in the cell (19). Iron‐chelating agents which have been investigated in the past include ethylenediamine tetra acetic acid (EDTA) (20) and desferrioxamine (DFO) (21). Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…At these doses in the normal colon, the dye is photodegraded too rapidly for the threshold light energy absorption to be reached, whereas in the tumor, which contains approximately twice as much CIAIPCS, the threshold dose is reached, making selective tumor destruction possible (Barr et al, 1990). A preliminary study showed that selective necrosis of malignant glioma cells in a tumor bed in mice can be achieved with ClAlPCS and red light, using treatment parameters that do not damage normal brain under conditions that mimic clinical practice (Sanderman et al, 1987). ClAlPCS was also evaluated for treatment of experimental intraocular melanoma in rabbit eyes.…”
Section: Phorodynamic Therapymentioning
confidence: 99%
“…During the past few years metalphthalocyanines have been evaluated with respect to their uptake and photosensitizing properties in neoplastic cells/tissues in vitro and in vivo (Ben-Hur and Rosenthal, 1985;Chan et al, 1986Chan et al, , 1988Chan et al, , 1990Sanderman et al, 1987;Peng et al, 1987Peng et al, , 1990aBrasseur et al, 1988;Paquette etal., 1988;Berg et al, 19896). However, the patterns and mechanisms of localization of different metal-phthalocyanine derivatives in tumor cells/tissues are not yet well understood.…”
mentioning
confidence: 99%